Imprints on the Resource Landscape: The Long History of Mining in the Arctic - Avango, Dag (Journal of Northern Studies, 2021)
For several years, public debates about the future of the Arctic have included the growing global needs in minerals and energy resources. To explain and manage this development, it is important to understand impacts of previous extractive industries in the north. Using theoretical approaches from economic geography and science and technology studies, the aim of this article is to describe and explain the growth of mining in the Arctic and its consequences for people and environments. How and why have minerals in the Arctic been constructed as natural resources? What systems have been built to extract them, and what were their consequences? How has the legacies of mining been managed when the extraction has ceased and why? The development of mining is explained as resulting from not only economic interests, but also geopolitical considerations, institutional frameworks and cultural-ideological trends. The same drivers are involved in the making of post-extraction futures and the way people relate to the mining legacies through environmental remediation, re-purposing and heritagization.